A Single Dose of Caffeine Ingestion Improves Physical and Cognitive Performance During A 1500-M Run Competition - Khcharem, Amir; Masmoudi, Liwa; Sahnoun, Zouheir (Health Nexus, 2024)
Caffeine is a psychoactive world widely used substance to improve physical and cognitive athletes’ performance. However, its relative impact during outdoor competitions is not well investigated. The present investigation aimed to assess the impacts of a single moderate dose of caffeine ingestion on physical and cognitive performance following a 1500-m running competition. Methods: Fifteen recreational runners performed two test sessions in a randomized order at 09:00 a.m. after ingesting 5 mg.kg-1 caffeine or a placebo. At each session, participants realized the competition of 1500-m running in a field setting. Before and after the race, they performed the correct detection and reaction-time tasks. Compared to placebo, caffeine ingestion improved 1500-m performance time (1.5%, p < .01), increased correct detections (10.6%, p < .01), and decreased reaction time (6.3%, p < .001) following the race. Caffeine consumption is an effective strategy to enhance athletes’ physical and cognitive performances during such running distances.